Plan de mercadeo de los productos lácteos elaborados en los talleres agroindustriales de la Espam MFL - Espinoza Sabando, Gabriel Hernán (2012)
The work aims to make a marketing plan in the production line of dairy ESPAM "MFL" and show the results of the implementation of the proposal, in order to solve the existing problem. This research was divided into four stages that allow an assessment in order to find new niche markets for the commercialization of these production lines with a new marketing approach that allows improving the business decisions and achieve better results in their management. The novelty is that given in the dairy shop ESPAM "MFL" never been developed and implemented a marketing plan to help the marketing of these products making strategize and develop marketing and business management. In applied research methods and new tools for this type of research, among which are: the computer software package REDATAM databases to manage high volume, enabling us to develop comparison and evaluation of population density Bolívar Canton, and developing evaluative matrices of different production lines of dairy products. SWOT is applied in order to define the competitive position of the workshop and to develop strategies according to the demands of the current market demands and marketing of dairy products. The research helped the dairy shop have a tool to help it improve its business decisions and to obtain better results. From the results, it is recommended to apply this work to the development of business strategies that enable them to work more closely with their opportunities the environment offers.